2014
DOI: 10.1158/1078-0432.ccr-13-2683
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Therapeutic Implications of Aromatase Expression in Lung Adenocarcinomas with EGFR Mutations

Abstract: Purpose: Lung adenocarcinomas among never-smokers are more common in females than in males. This implies that gender-dependent hormones promote smoking unrelated lung adenocarcinoma. We therefore investigated mRNA expression of aromatase, an intrinsic estrogen synthetase, in lung adenocarcinoma and assessed its correlation to clinicopathologic factors, including EGFR mutations and postsurgical prognosis.Experimental Design: Aromatase mRNA expression in primary tumor samples from 110 patients with lung adenocar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…A recent study underscores the emerging importance of aromatase expression in neoplastic tissues in addition to ER-positive breast carcinoma (15). This study examined CYP19A1 expression in patients with lung adenocarcinoma and suggests that aromatase expression is a prognostic factor for this disease in female subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study underscores the emerging importance of aromatase expression in neoplastic tissues in addition to ER-positive breast carcinoma (15). This study examined CYP19A1 expression in patients with lung adenocarcinoma and suggests that aromatase expression is a prognostic factor for this disease in female subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicopathological features, including age at surgery, sex, smoking history, tumor differentiation, pathological tumor-node-metastasis (TNM) stage (seventh edition of the lung cancer staging system), pleural or lymphovascular invasion, histological subtype (World Health Organization Classification 2015), surgical procedure, and epidermal growth factor receptor ( EGFR ) mutation status, were examined. EGFR status had been determined in tumor tissues using the peptide nucleic acid-locked nucleic acid (PNA-LNA) polymerase chain reaction clamp method (Mitsubishi Chemical Medience, Tokyo, Japan) in 235 specimens [25]. Briefly, systemic dissection of hilar and mediastinal lymph nodes was performed at the same time as pulmonary lobectomy.…”
Section: Methodsmentioning
confidence: 99%
“…Although there is only weak evidence that estrogen exposure to lung tissue induces lung cancer in clinical practice (22), several studies have demonstrated that intra-tumor aromatase expression (8,10,15,16,18,21) exhibits an association with poorer prognoses. The present study did not indicate statistically significant associations between aromatase expression and pathological invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on hormonal receptors due to patients with smoking-independent lung cancers being mainly female (3,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Estrogen exposure measured by an indirect method could only demonstrate a weak association between female hormone-associated factors and lung cancer (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation